Desenvolvimento e avaliação de filtros de poliacrilonitrila incorporados com nanopartículas e surfactantes para aplicação biocida na filtração de ar - Silva, Edilton Nunes da (Universidade Federal de São Carlos, 2022)
Suspended particulate matter in the air represents a significant health risk, potentially leading to severe respiratory diseases. Bioaerosols, including viruses, bacteria, and fungi, are also part of this particulate matter and can be inhaled, causing illnesses such as influenza, tuberculosis, and COVID-19. Electrospun filters are particularly effective for capturing these particulates due to their high surface area. Additionally, these filters can be enhanced by incorporating nanoparticles and surfactants into their fibers, which improves their filtration efficiency and imparts biocidal properties. This study focuses on developing a filtration medium using polyacrylonitrile (PAN) combined with compounds that provide biocidal characteristics and assessing how these compounds affect filtration performance. The compounds investigated include zinc oxide (ZnO) nanoparticles and surfactants like cetylpyridinium chloride (CPC), cetyltrimethylammonium bromide (CTAB), and sodium dodecyl sulfate (SDS). Electrospinning was employed to produce nanofibers at the nanometer scale. In the initial phase, electrospinning parameters were optimized using only ZnO. Nanofibers made from PAN at varying concentrations (8%, 9%, and 10% w/w) were combined with ZnO nanoparticles at different levels (5%, 10%, and 15%). Scanning electron microscopy (SEM) was used to measure fiber diameters, and a 2³ factorial design was applied to determine the optimal conditions for PAN and ZnO concentrations and voltage to produce nanofibers with the smallest diameters, enhancing filtration efficiency. In the subsequent phase, the optimized conditions were used to produce nanofibers containing 15% ZnO nanoparticles and surfactants (CTAB, CPC, and SDS) at concentrations of 1.5%, 2%, and 2.5%. Characterization of the solutions was conducted for viscosity and conductivity, and the resulting filters were analyzed using SEM, FTIR, TGA, DSC, and contact angle measurements. The bactericidal and virucidal activities of the filters were also assessed. The findings revealed that the filtering media had nanofiber diameters ranging from 431 to 712 nm, with filtration efficiencies reaching up to 99.80% and a pressure drop of 170 Pa. Furthermore, filters containing surfactants showed bactericidal effects greater than 99% against Staphylococcus aureus and Escherichia coli, and virucidal effects exceeding 99% against SARS-CoV-2.
Development and evaluation of polyacrylonitrile filters incorporated with nanoparticles and surfactants for biocidal application in air filtration
Keywords: Eletrofiação; Bactericida; Virucida; Nanopartículas; Filtros de ar; Surfactante; Óxido de zinco; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA